Given that x varies directly with y, we have that:
![x\text{ }\alpha\text{ y}](https://img.qammunity.org/2023/formulas/mathematics/college/ft09qellvaiiqez1sp6nab3fk8ginvdm6u.png)
Now, we replace the sign of proportionality with the contant k, as follows:
![x=ky](https://img.qammunity.org/2023/formulas/mathematics/college/b91e7l1m6piybwgau5d0r7jyq65iizkdp4.png)
Now, since we have a pair of values already given for x and y, we directly substitute those values into the equation above in order to obtain the value of the constant, as shown below:
![\begin{gathered} x=12\text{ and y = 3} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uvd64eaikww8lrs8jpd6l5ogp2ptdnrjc2.png)
Thus:
![\begin{gathered} x=ky \\ 12=k(3) \\ (12)/(3)=(k(3))/(3) \\ 4=k \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p3dhmkhs7qv22snz1pm5hyixn8mto5otbm.png)
Thus, we have the value of the constant k to be equal to 4.
Now, we have the equation to be:
![\begin{gathered} x=ky \\ x=4y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u99vfhhg02cns50odqiibuzerza07wsslf.png)
Finally, we make y the subject, as follows:
![\begin{gathered} x=4y \\ (x)/(4)=(4y)/(4) \\ (x)/(4)=y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/do8ybd6j0a5v0kl8fdhlfpm8c7em03gall.png)
Therefore:
![y=(x)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/bf3jbc25xpnes0614amfgg8wy1dh6homvc.png)
or:
![y=(1)/(4)x](https://img.qammunity.org/2023/formulas/mathematics/college/saxw4rytpyfyep91gz2920hkqcm5r7ic7n.png)
The value that goes into the numerator in the i